Self medication among medical and dental students in tertiary care teaching hospital of Udaipur, India - Chawda, Hiren M.; Panchasara, Ashwinkumar K. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Self‐medication involves acquiring and consuming medication without the advice of a physician and also resubmitting old prescriptions to purchase medicines. Inappropriate self‐medication causes increase cost of therapy and incidence of adverse drug reactions. Self-medication was significantly higher among undergraduate medical and paramedical students in India. Objective of the study was to evaluate the prevalence of self-medication and perception towards self-medication among the undergraduate medical and dental students. Methods: A pre-designed questionnaire collected the information pertaining to demographic details like age, gender, course, reason, pattern, indications, drugs used for self‐medication. It also included questions concerning their attitude, perception and safety regarding self-medication. Results: The prevalence of self - medication was 76.27%. Larger numbers of females were self-medicating (55.56%). The majority of the students’ self-medicated because of other advice (92.59%), there was statistically significant difference between the male and female medical students to use a previous prescription for the same illness. A total of 136 (76.83%) of the participants opined that self-medication was a part of self-care. Statistically significant differences between male and female students had been observed in safety variables like, “know side effects about your drug”, “increasing drug dose can be dangerous” and “in case of side effects physicians’ help must be sought”. Cold and Cough was the most common (60%) indication for self-medication. Conclusions: The prevalence of self-medication was higher among females. The majority of the students’ self-medicated because of other advice. The stringent policies should be required for medicines which can prevent the increasing trend of self-medicating.